Problema do Caixeiro Viajante com Seleção de Hotéis: Uma Revisão Sistemática da Literatura - de Sousa, Marques Moreira; Ochi, Luiz Satoru; Martins, Simone de Lima (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
The Traveling Salesperson Problem with Hotel Selection (TSPHS) is a novel variant of the classical Traveling Salesperson Problem. In this variant, the main objective is to minimize the number of trips and total traveled time. This problem is found in real scenarios like delivery of products by electric vehicles that need to be recharged along a tour. This systematic review of the literature aims to analyse techniques and trends to solve this logistic problem using combinatorial optimization. We have applied a search string related to TSPHS for three search engines, filtered 33 returned results and analyzed the proposed approaches to identify the following aspects: (i) characteristics of the solved problems, (ii) if statistics analyses have been performed for parameter tuning in case of heuristics approaches, (iii) characteristics of instances solved by exact methods and (iv) types of experiments. Furthermore, we have observed that the Lin-Kernighan heuristic performs well to generate initial solution for heuristics, the hotels order sequence has major impact on final solution quality and the complexity of this problem still represents for modern Information Systems a constraint to solve large instances using exact approaches.